Armenian Apocrypha relating to angels and biblical heroes - Stone, Michael E., 1938- (My University)
Michael E. Stone's latest book explores how the vivid and creative Armenian spiritual tradition shaped biblical stories to serve new needs. Stone edits and provides introductions, translations, and notes for Armenian manuscript texts relevant to the development and growth of biblical themes and subjects. Most of the texts translated are from previously unpublished manuscript witnesses
By Michael E. Stone. - Atlanta : SBL Press, [2016]. - xiv, 307 pages ; 24 cm. - Includes bibliographical references (pages 277-282) and indexes. - In English; with original Armenian texts translated into English
Տվյալները՝ ինտերնետային կայքից
https://www.pdfdrive.com/armenian-apocrypha-relating-to-angels-and-biblical-heroes-e182236111.html
Keywords: Abraham (Biblical patriarch); Judaism-Relations-Christianity; Christianity and other religions-Judaism; Apocryphal books-Translations into Armenian